The Influence of Effectiveness of Management, Work Culture, Trust and Engagement, towards Work Effectiveness of Employee Property Company at Jakarta - Dewi Tridasawarsa; Ma'ruf Akbar; Thamrin Abdullah (IJHCM (International Journal of Human Capital Management), 2019)
This study aims to measure and analyze the effect of management effectiveness, work culture, trust, and engagement on the work effectiveness of employees of family-based property companies in Jakarta. Of the 193 homogeneous employee populations spread in Jakarta, Cinere, Bogor and Tangerang, the samples were based on Slovin and the simple random sampling technique was 130 people. This study uses a quantitative approach with linear regression analysis, single test, and path analysis. From the results of the study, it can be seen that: (1) management effectiveness, work culture, and trust have a positive and significant direct effect on work effectiveness, (2) effectiveness of management and work culture indirectly affect work effectiveness through trust, (3) engagement is not effect directly or indirectly on work effectiveness. The results of the study found that Trust is the most influential and very significant variable in influencing the work effectiveness of employees in family companies. Conclusions obtained, namely transparency, honesty, and fairness, and high integrity can make work more effective.